2014
DOI: 10.1016/j.bjid.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hospital daily cleaning practices using ATP bioluminescence in a developing country

Abstract: This study suggests that visual assessment is not enough to ensure quality of the process and it is necessary to document the level of cleanliness by quantitative methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
2
16
0
1
Order By: Relevance
“…29 Surfaces in surgical ICUs were more likely to be contaminated with MRSA and VRE and particular attention is needed to improve cleaning at these units. 30 In partial agreement with our results Boyce et al 3 found that after cleaning of 100 high touched surfaces, 24% were still contaminated with MrSa, and 16% still yielded VRE. While Goodman et al 31 reported that environmental culture positive for MRSA or VRE were 45% before educational intervention versus 27% after educational intervention.…”
Section: Standard Precautions Compliance In Icussupporting
confidence: 92%
See 2 more Smart Citations
“…29 Surfaces in surgical ICUs were more likely to be contaminated with MRSA and VRE and particular attention is needed to improve cleaning at these units. 30 In partial agreement with our results Boyce et al 3 found that after cleaning of 100 high touched surfaces, 24% were still contaminated with MrSa, and 16% still yielded VRE. While Goodman et al 31 reported that environmental culture positive for MRSA or VRE were 45% before educational intervention versus 27% after educational intervention.…”
Section: Standard Precautions Compliance In Icussupporting
confidence: 92%
“…Significant improvements were obtained after educational intervention as 97.45% of surfaces became clean. These results are in agreement with those of Zambrano et al 30 who evaluated environmental cleaning of 198 hospital surfaces by aTP bioluminescence and not for citation purposes…”
supporting
confidence: 92%
See 1 more Smart Citation
“…38 In recent years, several studies on the application of ATP-activity for monitoring microbial loads in environmental samples (including surface and device swabs, aqueous humidifier samples, and ready-toeat foods) were evaluated and was reported as a useful tool as it gave a good correlation with the standard methods. [39][40][41] The intervention program for reducing the microbial concentration in the air and on the surface areas in ambulances should emphasize the need for a ventilation improvement strategy, and improvement in the cleaning program of the ambulance environment, including medical instruments, seats, the floor, and air conditioning units. Additionally, the use of standard precautions, including hand hygiene and effective personal protective equipment (PPE) will prevent cross infection and save ambulance personnel's lives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is known that, after C&D procedures, many more surfaces considered as dirty by ACC are seen as clean by visual inspection when compared to another non-microbiological method (ATP-bioluminescence, fluorescent marker) (4,13) . Studies suggest that visual assessment is not sufficient to ensure the quality of the process, and it is less efficient than quantitative methods in raising awareness about the need to improve sanitation practices (20) . The use of ATP-bioluminescence to assess and have feedback of results leads to greater awareness, collaboration, communication and education of cleaning and nursing staffs, and therefore, it improves the efficiency of practices (21)(22) .…”
Section: Discussionmentioning
confidence: 99%